Appealing to Tacit Knowledge and Axiology to Enhance Medical Practice in the COVID-19 Pandemic: A Systematic Review and Hermeneutic Bioethical Analysis - Serrano-Zamago, Ana-Beatriz; Altamirano-Bustamante, Myriam M. (Frontiers in Public Health, 2021)
The pressure of COVID-19 pandemic, epidemiological and demographic changes, personnel-patient relationship in healthcare, and the development of biotechnologies does not go unnoticed by the healthcare professional. Changes are so wide and at a high rate that guidelines and mere scientific knowledge are not sufficient to lead actions, thus the experiential aspects in the configuration of an ethos present as a fundamental part of the resources to deal with critical scenarios, such as a pandemic. In this regard, the recognition of tacit knowledge as a way of teaching and learning skills related to ethical aspects such as principles, virtues and values, reveals as a fundamental part of the clinical field amid of the COVID-19 pandemic. Ethical-tacit knowledge is outlined as an active and integral process. However, for it to work in favor of clinical practice in limited situations such as a pandemic, it is necessary to unpack Values-Based Medicine using the qualitative approach as a vector, which allows to take from the experiences of healthcare personnel that which remains in a level of consciousness that does not let them to express it. We explored and analyzed the literature referring to ethical-tacit knowledge through a two-fold analysis -first a systematic review following PEO and PRISMA approaches and secondly a hermeneutic bioethical analysis- to identify gaps in the investigation about tacit knowledge, taking pediatric endocrinology as an example given the impact it has in individuals throughout their life. This methodology helped us to unravel the content of the articles and identify how ethical-tacit issues relate to medical practice in pandemic. The analysis of ethical-tacit knowledge in medicine is a recent phenomenon and is in full development. While ethics justifies actions insofar as they perform desirable values, according to preferable ends, tacit ethical knowledge examines from personal experience (observe or carry out a practice) the actions that define the foundations of moral judgments (values and virtues).